Cultivation of Bat Willows in Kulu - Singh, D. P. (Indian Forester, 1953)
Preliminary trials on cultivation of English and Kashmir bat willows (both obtained in the form of cuttings from Kashmir) have given encouraging results in Kulu forest division. The problem is being pursued with full zeal and vigour and if the success attained so far is maintained in coming years, the future of sports' industry in the Punjab is assured.